Next level of pharmacists: the guardian of the medicines / Ahmad Najib Afandi - Afandi, Ahmad Najib (Faculty of Pharmacy, 2023)
I have spent four years of my life committing to the acquisition of the knowledge and crafts to be a nobleman – a pharmacist, only to be taken aback by the harsh reality that, an illegal immigrant was giving counseling (I eavesdropped the whole conversation) to a customer buying Misoprostol, illegally at a secluded spot in a night market.